THE EFFECT OF DEBT TO EQUITY RATIO (DER), ASSET GROWTH (AG), AND FIRM SIZE (FS) ON DIVIDEND PAYOUT RATIO (DPR) - Herry Krisnandi; Elwisam; Melati; Kumba Digdowiseiso; Jumadil Saputra (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
The objective of this study is to examine the impact of Debt to Equity Ratio (DER), Asset Growth (AG), and Firm Size (FS) on the Dividend Payout Ratio (DPR) in companies that are listed on the LQ 45 index on the Indonesia Stock Exchange. The study focuses on investigating the determinants of dividend distribution policies, particularly in relation to financial structure, asset growth, and company size. The research methodology entails conducting a Systematic Literature Review (SLR) to analyze data. This involves examining previous research that explores the impact of these variables on dividend distribution policies. The analysis findings indicate that DER, AG, and FS exert a substantial impact on the DPR. The Dynamic Efficiency Ratio (DER) has a positive influence on the Dynamic Performance Ratio (DPR), whereas the Asset Growth (AG) and Firm Size (FS) have a positive and substantial influence on the DPR. The research concludes that dividend distribution policy is significantly influenced by financial structure, asset growth, and company size. Hence, it is recommended that companies thoroughly evaluate these factors when developing dividend distribution policies to enhance company worth and bolster investor trust.